Rational construction of metal-organic framework derived dual-phase doping N-TiO2 plus S-carbon yolk-shell nanodisks for high-performance lithium ion batteries. (1st June 2023) - Cai, Chen; Yao, Zhujun; Xiang, Jiayuan; Chang, Xinhao; Yao, Weilin; He, Linxuan; Ruan, Lingfeng; Chen, Zihang; Shi, Juntao; Liu, Tiancun; Shen, Shenghui; Xie, Haijiao; et al.
Highlights: A novel structure of porous yolk-shell nanodisks constructed by secondary TiO2 nanosheets is proposed. Synergic effects of N doped TiO2, S doped MOFs-derived carbon and conductive Ni metal are studied. The effect of the dual-phase doping strategy on Li + adsorption energy is investigated. N-TiO2 /S-C/Ni as an anode for lithium ion batteries exhibits great electrochemical properties. Abstract: Known as a low-strain anode material for lithium ion batteries (LIBs), the poor electronic/ionic conductivity of TiO2 is threatening to achieve satisfactory lithium ion storage performance. Herein, dual-phase doping combined with structure design strategy is carried out to construct yolk-shell nanodisks decorated with N-doped TiO2 nanosheets, S-doped carbon and conductive Ni nanoparticles (N-TiO2 /S-C/Ni) to realize enhanced electrochemical performance. Thanks to the N-doping in TiO2 and S-doping in metal organic frameworks (MOFs) derived carbon, the lithium ion adsorption energy of the composite can be enhanced to promote kinetic process, which is proved by density functional theory (DFT). Moreover, the elaborate yolk-shell structure with great specific surface area and abundant holes will induce plentiful sites for electrochemical reaction and make the transport pathway of ions/electrons shorter. Profiting from the above appealing features, the N-TiO2 /S-C/Ni electrode displays a high capacity of 649 mAh g −1 at 0.1 A g −1 and 441 mAh g −1 at 1 A g −1 after cycling with the Coulombic efficiency of nearly 100%. On top of that, TiO2 //LiFePO4 full batteries are assembled to estimate the practical value of N-TiO2 /S-C/Ni. Graphical abstract: Image, graphical abstract